Alternative inert gas washout outcomes in patients with primary ciliary dyskinesia. Issue 1 (26th January 2017) - Nyilas, Sylvia; Schlegtendal, Anne; Singer, Florian; Goutaki, Myrofora; Kuehni, Claudia E.; Casaulta, Carmen; Latzin, Philipp; Koerner-Rettberg, Cordula
The lung clearance index (LCI) derived from a nitrogen multiple breath washout test (N2 -MBW) is a promising tool to assess small airways disease in primary ciliary dyskinesia, but it is difficult to apply in routine clinical settings because of its long measuring time. In this study, we aimed to assess alternative indices derived from shorter washout protocols. 49 patients with primary ciliary dyskinesia (mean age 14.7±6.6 years) and 37 controls (mean age 14.3±1.4 years) performed N2 -MBW and double-tracer gas (DTG) single-breath washout tests. Global (LCI and moment ratio (M2 /M0 )), conductive ( S cond ) and acinar ventilation inhomogeneity (DTG Slope III (SIII -DTG)) were determined for each individual. The main outcomes were 1) the ability to detect abnormal lung function from washout indices (>1.64 z-scores) and 2) measurement duration. The prevalence of abnormal values for LCI2.5% was 37 out of 47 (79%), for LCI5% was 34 out of 47 (72%), for M2 /M0 was 34 out of 47 (72%), for S cond was 36 out of 46 (78%) and for SIII -DTG was 12 out of 35 (34%). Mean±sd duration of measurement was 19.8±11.2 min for LCI2.5%, 10.8±4.6 min for LCI5% and 8.6±2.3 min for S cond . Compared to standard LCI2.5%, ventilation inhomogeneity was detected by LCI5%, moment ratio and S cond with comparable sensitivity while measurement duration was significantly shorter. Longitudinal studies will show which outcome is most suitable and practical in terms of sensitivity, duration and variability within the course of primary ciliary dyskinesia lung disease. Alternative washout outcomes of shorter test duration detect ventilation inhomogeneity in patients with PCD http://ow.ly/ffnL307OzWX